2020
DOI: 10.1210/jendso/bvaa019
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Impact of FSH Glycosylation Variants on FSH Receptor-stimulated Signal Transduction and Functional Selectivity

Abstract: FSH exists as different glycoforms that differ in glycosylation of the hormone-specific β-subunit. Tetra-glycosylated FSH (FSH24) and hypo-glycosylated FSH (FSH18/21) are the most abundant glycoforms found in humans. Employing distinct readouts in HEK293 cells expressing the FSH receptor, we compared signaling triggered by human pituitary FSH preparations (FSH18/21 and FSH24) as well as by equine FSH (eFSH), and human recombinant FSH (recFSH), each exhibiting distinct glycosylation patterns. The potency in eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 93 publications
5
59
0
Order By: Relevance
“…Teleologically speaking one must assume that the unique human sialylation has some role. It is not possible to know if the ratio of Rekovelle ® glycoforms is similar to the reference preparation Gonal-F ® because that information is not publicly available, albeit it is known that Gonal-F ® is primarily bi-glycosylated ( 9 ) ( Figure 1 ). Without such information it is not possible to attribute the longer half-life to any particular structural feature, particularly since the inventors already demonstrated that α2,6 sialic acid only follitropin was cleared more rapidly than any other preparation of follitropin.…”
Section: Structural Aspects Of Follitropin Which Affect Pharmacokinetics Pharmacodynamics and Clinical Response In Comentioning
confidence: 99%
See 4 more Smart Citations
“…Teleologically speaking one must assume that the unique human sialylation has some role. It is not possible to know if the ratio of Rekovelle ® glycoforms is similar to the reference preparation Gonal-F ® because that information is not publicly available, albeit it is known that Gonal-F ® is primarily bi-glycosylated ( 9 ) ( Figure 1 ). Without such information it is not possible to attribute the longer half-life to any particular structural feature, particularly since the inventors already demonstrated that α2,6 sialic acid only follitropin was cleared more rapidly than any other preparation of follitropin.…”
Section: Structural Aspects Of Follitropin Which Affect Pharmacokinetics Pharmacodynamics and Clinical Response In Comentioning
confidence: 99%
“…The crystal structures of the follitropin – hormone binding domain, or the follitropin – full extracellular domain also lack carbohydrate at this locus following endoglycosidase treatment. Thus, it is an open question whether glycosylation of the β-subunit affects the structure of follitropin and yet it has clearly been shown to affect its pharmacodynamics ( 9 , 77 ). Moreover it does appear that hypoglycosylated FSH has greater accessibility to FSHR or causes structural shifts in FSHR that unveil additional binding sites ( 77 ).…”
Section: Structural Aspects Of Follitropin Which Affect Pharmacokinetics Pharmacodynamics and Clinical Response In Comentioning
confidence: 99%
See 3 more Smart Citations